Kontrol Glikemik dan Penilaian Risiko Kardiovaskular: Studi Kadar HbA1c dan Hs-CRP pada Diabetes Melitus Tipe 2 - Putri, Mustika Anggiane; Amani, Patwa; Adriani, Donna; Imran, Yudhisman (Fakultas Kedokteran Universitas Trisakti, 2025)
Background Type 2 diabetes mellitus (T2DM) is a major risk factor for cardiovascular disease. Patients with diabetes have a 2-4 times higher risk of developing coronary heart disease compared to those without diabetes. Cardiovascular complications are the leading cause of illness and death in diabetic patients, with cardiovascular disease-related deaths making up 65-75% of all deaths in this group. Poor glycemic control is a key factor in the development of cardiovascular problems in diabetes. Chronic high blood sugar levels activate various harmful mechanisms, including increased oxidative stress, systemic inflammation, endothelial dysfunction, and faster atherosclerosis. Hemoglobin A1C (HbA1C), a marker of long-term blood sugar control, strongly correlates with the risk of both microvascular and macrovascular complications in diabetes. This study aims to examine the relationship between glycemic control, as measured by HbA1C, and systemic inflammation, assessed through Hs-CRP, as predictors of cardiovascular risk in patients with type 2 diabetes mellitus. Methods An analytical cross-sectional study was conducted on 53 T2DM patients at the Prolanis Clinic in East Jakarta, using purposive sampling. HbA1c was measured with the HPLC method, and Hs-CRP with the Turbidimetric Immunoassay method at PRODIA laboratory. Correlation analysis was performed using Spearman's correlation test. Results The study showed an average HbA1C level of 7.2% and an average Hs-CRP level of 2.9 mg/L. Statistical analysis indicated a significant correlation between HbA1C and Hs-CRP (p-value = 0.014), with a Spearman correlation coefficient of 0.336. Conclusions There is a significant positive correlation between HbA1c and Hs-CRP levels.